MATH SOLVE

2 months ago

Q:
# For f(x) = 3x +1 and g(x) = x2 – 6, find (f – g)(x). A. x2 – 3x – 7 B. –x2 + 3x + 7 C. –x2 + 3x – 5 D. 3x2 – 17

Accepted Solution

A:

Answer:

(f-g) (x) = -x² + 3x + 7

Explanation:

We are given that:

f (x) = 3x + 1

g (x) = x² - 6

We want to find (f-g) (x), we can simply obtain the result by subtracting g (x) from f (x) as follows:

(f-g) (x) = f (x) - g (x)

(f-g) (x) = 3x + 1 - (x²-6)

(f-g) (x) = 3x + 1 - x² + 6

(f-g) (x) = -x² + 3x + 7

Hope this helps :)

(f-g) (x) = -x² + 3x + 7

Explanation:

We are given that:

f (x) = 3x + 1

g (x) = x² - 6

We want to find (f-g) (x), we can simply obtain the result by subtracting g (x) from f (x) as follows:

(f-g) (x) = f (x) - g (x)

(f-g) (x) = 3x + 1 - (x²-6)

(f-g) (x) = 3x + 1 - x² + 6

(f-g) (x) = -x² + 3x + 7

Hope this helps :)